2018
DOI: 10.1155/2018/6518329
|View full text |Cite
|
Sign up to set email alerts
|

Passenger Mobility in a Discontinuous Space: Modelling Access/Egress to Maritime Barrier in a Case Study

Abstract: The present study analyses a transport system in a discontinuous space. Classical specifications of transport models cannot be applied directly when evaluating the influence of territorial discontinuity and related barriers on user behaviour. Adjustments are required for this specific case because studies relative to discontinuous spaces are limited. The influence concerns the different travel components (access, barrier, on board, and egress) and could impact travel choices (departure time, destination, mode,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…A 2019 travel survey found that women perform double the number of trips for domestic tasks, such as taking children to school, when compared to men [19]. Unfortunately, common specifications of transport models should be adjusted for specific cases [20], such as taking into account the patterns between residential households' location and mobility choices [21]. In the context of gender equality, these specifications should clearly consider family dynamics.…”
Section: Women's Mobility and Travel Behaviourmentioning
confidence: 99%
“…A 2019 travel survey found that women perform double the number of trips for domestic tasks, such as taking children to school, when compared to men [19]. Unfortunately, common specifications of transport models should be adjusted for specific cases [20], such as taking into account the patterns between residential households' location and mobility choices [21]. In the context of gender equality, these specifications should clearly consider family dynamics.…”
Section: Women's Mobility and Travel Behaviourmentioning
confidence: 99%
“…Using the survey data from the Dutch railway, Debrezion et al [34] found that only 47% of the passengers choose their nearest station. Birgillito et al used the stochastic utility model to study the main variables that affect passenger choice and their relative weights in discontinuous spaces [35]. is study does illustrate that the boundary of station catchment areas also depends on the access to facilities and services at stations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The high level of the ITS Part 4-transport monitor and management can get the whole information and set the objectives and constraints on Part 3. Many new developed models, algorithms, and equipment could be integrated in the architecture [47,48].…”
Section: Of 18mentioning
confidence: 99%